Tuntutan Keadilan Penyelidikan Kasus Kematian Arya Daru yang Belum Terjawab oleh Negara dalam Perspektif HAM - Nia Lestina; Nur Fadilah Sari; Siti Maisyurah; Adolfina Durian; Carini Carini (Federalisme: Jurnal Kajian Hukum dan Ilmu Komunikasi, 2025)
The death of Diplomat Arya Daru has opened up a space for reflection on the extent to which the state has fulfilled its investigative obligations to guarantee the right to life and the right to truth, as fundamental human rights. The delay and secrecy of the investigation indicate institutional accountability issues and weak mechanisms for protecting the rights of victims and their families. This study uses a doctrinal legal approach to examine the state's position through the perspectives of positive obligations theory and distributive justice, which emphasize the state's active obligation to protect, disclose, and restore citizens' basic rights. The analysis shows that the lack of transparency in the investigative process not only violates the principle of justice but also reflects inequality in the distribution of legal protection. The state should ensure that justice does not stop at the formal level but is realized through transparent, independent investigations based on factual truth. In the context of human rights, the state's passive attitude towards alleged violations of the right to life can be interpreted as a denial of its constitutional and moral responsibilities. This study emphasizes that fulfilling the right to truth is an integral part of distributive justice and is non-negotiable. Thus, the Arya Daru case is an important indicator for assessing the state's seriousness in realizing a legal system that is just, accountable and oriented towards respecting human dignity.